Iterative reduction of the Dirichlet problem to the Neumann problem - Pankov, A. A.; Pankova, T. E. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
An iteration procedure for reduction of the Dirichlet boundary-value problem to the Neumann problem is suggested. Estimates of the rate of convergence are established.